Renal-hepatic-pancreatic dysplasia-1 with a novel NPHP3 genotype: a case report and review of the literature - Hui Zhu; Zhi-hui Zhao; Shu-yao Zhu; Fu Xiong; Li-hong He; Yong Zhang; Jin Wang (BMC, 2022)
Abstract Background Renal-hepatic-pancreatic dysplasia type 1 (RHPD1) is a rare sporadic and autosomal recessive disorder with unknown incidence. RHPD1 is caused by biallelic pathogenic variants in NPHP3, which encode nephrocystin, an important component of the ciliary protein complex. Case presentation In this case report, we describe a male newborn who was confirmed by ultrasound to have renal enlargement with multiple cysts, pancreatic enlargement with cysts, and increased liver echogenicity, leading to the clinical diagnosis of RHPD. In addition, a compound heterozygous pathogenic variant, namely, NPHP3 c.1761G > A (p. W587*) and the c.69delC (p. Gly24Ala24*11) variant, was detected by WES. The patient was clinically and genetically diagnosed with RHPD1. At 34 h of life, the infant died of respiratory insufficiency. Conclusion This is the first published case of RHPD1 in China. This study broadens the known range of RHPD1 due to NPHP3 pathogenic variants.